Zidovudine-Based Treatments Inhibit the Glycosylation of ADAM17 and Reduce CD163 Shedding From Monocytes. (1st September 2018) - Chen, Song; Wang, Xiaoyu; Zhu, Haipeng; Tang, Qin; Du, Wei; Cao, Huanhuan; Lai, Chunhui; Guo, Weizhong; Fu, Linchun; Lu, Wei
Abstract : Background: sCD163, a biomarker of monocyte-macrophage activation, has been identified as a predictor of all-cause mortality in treated HIV-infected individuals. Nevertheless, little is known about whether different antiretroviral drugs differentially regulate sCD163 levels and monocyte activation. Methods: A total of 123 patients receiving zidovudine (ZDV)-based (n = 55) or tenofovir disoproxil fumarate (TDF)-based (n = 68) antiretroviral regimens were enrolled, and their viral loads, CD4 counts, as well as plasma sCD163 and sCD14 levels were quantified. Twenty-eight (14 in each group) patients donated additional blood samples for flow cytometry and gene expression analyses using purified monocytes. THP-1 cultures were also used to investigate the effect of ZDV on ADAM17, which is responsible for CD163 shedding. Results: As compared to the TDF-treated group, the ZDV-treated group had lower plasma sCD163 levels and higher CD163 expression on CD14++CD16 − monocytes. Five metabolic-inflammatory genes exhibited significantly different expression levels between purified monocytes of the ZDV and TDF groups ( IL-6, 2.90-fold lower in ZDV group, P < 0.001; iNOS, 1.81-fold higher; CX3CR1, 1.72-fold lower; MIP-1β, 1.10-fold lower; and PPARγ-1, 1.36-fold higher, P < 0.05). Moreover, we show that ZDV treatment increases the surface expression of CD163 in cultured THP-1 cells, accompanied by the inhibition of glycosylation and surface expression of ADAM17. Conclusions: Compared with TDF treatment, ZDV treatment causes lower plasma sCD163 levels, probably by inhibiting the glycosylation of ADAM17 and CD163 shedding. Our results show that ZDV functions as an ADAM17 inhibitor in vivo and extend our understanding of its immune-modulatory effects and adverse effects. Abstract : Supplemental Digital Content is Available in the Text.